2012
DOI: 10.1002/app.38212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biological degradation by termites on the flexural properties of pinewood residue/recycled high‐density polyethylene composites

Abstract: Wood-plastic composites (WPCs) are considered to be highly durable materials and immune to any type of biological attack. However, when one of these composites is exposed to accelerated weathering, its surface is affected by the appearance of cracks, which constitute an ideal access route for biotic agents. Although the destruction of wood caused by termites is recognized worldwide, information on their effects on WPC-based products is scarce. Thus, in this study, we aimed to examine the effects of termite att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
4
10
1
Order By: Relevance
“…Figure 2 shows the dynamical DSC curves of the cast-extruded bio-HDPE films, whereas Table 3 summarizes the main thermal parameters obtained from the curves. One can observe that, in all cases, the polyolefin melted sharply in a single peak at approximately 132 • C. A similar melting profile has been observed previously for this polyolefin, regardless of the origin and the methodology followed to prepare the articles [37,44]. It can also be seen that the ∆H m values of bio-HDPE slightly reduced as the GA content in the green polyolefin increased.…”
Section: Thermal Properties Of the Ga-containing Bio-hdpe Filmssupporting
confidence: 82%
“…Figure 2 shows the dynamical DSC curves of the cast-extruded bio-HDPE films, whereas Table 3 summarizes the main thermal parameters obtained from the curves. One can observe that, in all cases, the polyolefin melted sharply in a single peak at approximately 132 • C. A similar melting profile has been observed previously for this polyolefin, regardless of the origin and the methodology followed to prepare the articles [37,44]. It can also be seen that the ∆H m values of bio-HDPE slightly reduced as the GA content in the green polyolefin increased.…”
Section: Thermal Properties Of the Ga-containing Bio-hdpe Filmssupporting
confidence: 82%
“…Finally, after 12 months of exposure was possible to distinguish three small endotherms peaks before melting the PP, that could be related to the secondary recrystallization of short polymer segments produced by chain-breaking reactions on polypolypropylene after natural ageing. This behavior was also observed by López-Naranjo et al [25], who observed that because of accelerated weathering new thermal energy absorption peaks (shoulders at about 110 ºC) appeared on their material. In Figure 7 are shown comparative TGA curves of the composites before and after natural ageing and Table 3 shows the TGA numeric results.…”
Section: Influence Of Natural Ageing On the Morphology Changessupporting
confidence: 79%
“…On the other hand, the compounds formed by the photo-oxidation of lignin were solubilized by water and lixiviated. These results are in good agreement with what is reported in the literature (Stark and Matuana 2004;Stark 2006;Fabiyi et al 2008;Fabiyi and McDonald 2010;López-Naranjo et al 2013). Regarding the carboxylate anion index shown in Table 4, it is generally observed that it was similar for the materials with 0% coupling agent (UV-irradiated or not), subjected to 0 and 4 MADCs.…”
Section: Fourier Transform Infrared Spectroscopysupporting
confidence: 82%
“…The peak intensities were normalized using the peak at 2917 cm -1 , corresponding to the alkane C-H stretching vibrations of methylene groups. This peak was chosen as a reference because it changed the least with weathering (Stark and Matuana 2004;López-Naranjo et al 2013). The amount of lignin and the possibility of hydrolysis in the samples were respectively quantified by means of the lignin and carboxylate anion indexes (the carboxylate anion is a hydrolysis product).…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%